The Determinants of Television Audience for Professional Cycling: The Case of Spain. (January 2015) - Rodríguez, César; Pérez, Levi; Puente, Víctor; Rodríguez, Plácido
This research is intended to assess the determinants of the television (TV) audience in Spain for professional cycling. Our data refer to cycling races broadcast on several Spanish TV channels and make it possible to compute three different audience variables: rating, share, and number of viewers . The most original contributions of this research are the new indicators of competitive balance for cycling races that are proposed here. The outcomes show that audience ratings depend mainly on the following features: competitive balance, the type of stage and race, the nationality of the race leader, and inertial behaviors on the part of viewers.